Cardiotoxicity of Anthracyclines - Cardinale, Daniela; Iacopo, Fabiani; Cipolla, Carlo Maria (Frontiers in Cardiovascular Medicine, 2020)
Cardiotoxicity is a relevant complication that may compromise the clinical use of anthracyclines, affecting the quality of life and overall survival in cancer patients, independently of the oncological prognosis. The paper provides an overview of anthracycline-induced cardiotoxicity in terms of definition, classification, incidence, risk factors, possible mechanisms, diagnosis, and treatment. We also reported effective strategies for preventing cardiotoxicity. Furthermore, we discussed the limitation of current approaches, the need for a new classification, for early detection and treatment of cardiotoxicity. Probably, anthracycline-induced cardiotoxicity is a unique and continuous phenomenon starting with myocardial cell injury, followed by progressive left ventricular ejection fraction (LVEF) decline that, if disregarded and not cured progressively leads to overt heart failure. Anthracycline-induced cardiotoxicity can be detected at an early preclinical phase, very much before the onset of heart failure symptoms or before LVEF drops. The role of troponins in identifying subclinical cardiotoxicity and treatment with angiotensin-converting enzyme inhibitors to prevent LVEF reduction is an effective strategy that has emerged in the last fifteen years. If cardiac dysfunction has already occurred, partial or complete LVEF recovery may still be obtained if cardiotoxicity is detected early and heart failure treatment is promptly initiated.